2021
DOI: 10.3390/s21113843
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker-Informed Machine Learning Model of Cognitive Fatigue from a Heart Rate Response Perspective

Abstract: Cognitive fatigue is a psychological state characterised by feelings of tiredness and impaired cognitive functioning arising from high cognitive demands. This paper examines the recent research progress on the assessment of cognitive fatigue and provides informed recommendations for future research. Traditionally, cognitive fatigue is introspectively assessed through self-report or objectively inferred from a decline in behavioural performance. However, more recently, researchers have attempted to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 138 publications
(217 reference statements)
0
8
0
Order By: Relevance
“…Cognitive fatigue is a psychological state characterized by the subjective feelings of tiredness, and impaired ability to think, memorize, and concentrate. [ 30 , 31 ] Cognitive fatigue is strongly associated with CRF. Eight studies reported the efficacy of ginseng oral administration and ginseng injections on cognitive fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…Cognitive fatigue is a psychological state characterized by the subjective feelings of tiredness, and impaired ability to think, memorize, and concentrate. [ 30 , 31 ] Cognitive fatigue is strongly associated with CRF. Eight studies reported the efficacy of ginseng oral administration and ginseng injections on cognitive fatigue.…”
Section: Resultsmentioning
confidence: 99%
“…Since it has been shown that cognitive exertion has a negative carryover effects on physical performance 49 and that physiological states correlate with cognitive fatigue 50 , physiological measures during pain stimulation were also collected to examine possible subsequent effects. Therefore, during the main experiment, we continuously recorded physiological responses to stimuli from their left hand, such as skin conductance (EDA) and heart rate.…”
Section: Methodsmentioning
confidence: 99%
“…Since it has been shown that cognitive exertion has a negative carryover effects on physical performance 9 and that physiological states correlate with cognitive fatigue 40 , physiological measures during pain stimulation were also collected to examine possible subsequent effects. Therefore, during the main experiment, we continuously recorded physiological responses to stimuli from their left hand, such as skin conductance (EDA) and heart rate.…”
Section: Methodsmentioning
confidence: 99%